EFFECTS OF SPONSOR-EVENT CONGRUENCE ON BRAND IMAGE, ATTITUDE TOWARD THE BRAND, AND PURCHASE INTENTION: AN EMPIRICAL ANALYSIS IN THE CONTEXT OF SPORT SPONSORSHIP - Park, Jun Young; Sihombing, Sabrina Oktaria (Jurnal Aplikasi Manajemen, 2020)
Event sponsorship is considered as one major marketing strategy. Companies investing in sponsorship are growing rapidly. However, research on sponsorship has not been done in the depth management aspects of a sports organization and has been concentrated in specific areas. Thus, this research fills the gap by conducting the study to analyze the relationship between sponsor-event congruence on brand image, attitude toward the brand, and purchase intention in the context of sport sponsorship event in Indonesia. Questionnaires were distributed by applying a personally administered questionnaire to 200 respondents who participated in that event. Data were analyzed through structural equation modeling method. Results showed that there are 4 out of 6 hypotheses were supported. Those hypotheses are: there is a positive relationship between sponsor-event congruence and attitudes toward the brand; there is a positive relationship between attitudes toward the brand and purchase intention, there is a positive relationship between brand image and attitudes toward the brand, and there is a positive relationship between sponsor-event congruence and purchaseintention.